2019
DOI: 10.1007/s10803-019-04250-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Response Diversity to Intraverbals in Children with Autism Spectrum Disorder

Abstract: The purpose of this study was to evaluate the effects of intraverbal prompts on response diversity and novelty in intraverbals posed to children with autism spectrum disorder (ASD). The intraverbal prompts involving function, feature, and class (FFC) of an item were used in the training of three questions requiring multiple responses. Two Chinese boys with ASD (aged 5-6 years) served as participants. A multiple-probe across three behaviors design was employed. The results indicated that the intraverbal prompts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(46 reference statements)
0
3
0
1
Order By: Relevance
“…In previous studies on teaching divergent intraverbal responding to participants with ASD, divergent responding for each instructional target has generally been absent until taught explicitly (Braam & Poling, 1983; Cihon et al., 2017; Feng et al., 2017; Goldsmith et al., 2007; Lee et al., 2017, 2020; Luciano, 1986). In the present study, by contrast, directly teaching divergent intraverbal responding to FFC questions resulted in the emergence of divergent responses to additional FFC questions without any direct instruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies on teaching divergent intraverbal responding to participants with ASD, divergent responding for each instructional target has generally been absent until taught explicitly (Braam & Poling, 1983; Cihon et al., 2017; Feng et al., 2017; Goldsmith et al., 2007; Lee et al., 2017, 2020; Luciano, 1986). In the present study, by contrast, directly teaching divergent intraverbal responding to FFC questions resulted in the emergence of divergent responses to additional FFC questions without any direct instruction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have addressed convergent and divergent control over intraverbal responses for participants with ASD (for a review, see Stauch et al., 2017). Studies on divergent control have demonstrated that tact (Alzrayer, 2020; Braam & Poling, 1983; Cihon et al., 2017; Feng et al., 2017; Goldsmith et al., 2007; Luciano, 1986), echoic (Braam & Poling, 1983), and intraverbal (Lee et al., 2017, 2020) prompts, combined with either transfer of stimulus control procedures or fluency training with prompts present (Cihon et al., 2017), can be used to successfully establish divergent intraverbal responding to a variety of questions about function, feature, and class (FFC). Further, variability of divergent intraverbal responding has been shown to increase when instructive feedback (Carroll & Kodak, 2015) and lag reinforcement schedules (Contreras & Betz, 2016) are incorporated into instruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Em uma revisão bibliográfica realizada por Esteves et al (2014), sobre o ensino de tato, mando vocal e ecoico, na base de dados do periódico JABA, verificou-se que nos anos de 1968 a 2012 houve uma tendência decrescente dos estudos envolvendo ensino de ecoico, principalmente a partir da década de 1990 e uma maioria deles (40 artigos), citou o ecoico como um prompt para ensino de outros operantes verbais (tato e mando). De fato, várias pesquisas utilizam o ecoico apenas como prompt, ou seja, como parte da variável independente nos estudos que objetivam, principalmente, o ensino de mando, tato e intraverbal (Swerdan & Rosales, 2015;Kisamore et al, 2016;Pérez-Gonzáles & García-Asenjo, 2016;Santos & Souza, 2016;Dass et al, 2018;Shillingsburg et al, 2018;Lee et al, 2020).…”
Section: Introductionunclassified